Enhancements of E-learning system by using social network features - Mahmood, Jamilah (2013)
E-learning that is used in the organization is found to be lack of knowledge sharing elements. Instead of using e-learning, user tends to use other alternatives site like social network to share knowledge. The knowledge sharing barriers in e-learning are identified from the analysis on past papers and questionnaire. The barriers found are willingness to share, changing organization culture, social relationship, features is difficult to use, limited functions, limited user access, knowledge evaluation and as well as the representation of features are not interesting. However, social network is found to have a strong relationship with knowledge sharing and its features are useful in solving the technology problems. It can facilitate knowledge sharing in two ways, which are by increasing knowledge reuse within users and by eliminating the reliance on formal liaison structures. The features of social network are analysed and enhancements of e-learning are proposed. The enhancements are evaluated by using questionnaire and interview. The results found that in order to enhance knowledge sharing in e-learning, the organization should embedded the knowledge sharing culture in student activities and promote the existing best features of e-learning to users. Besides, e-learning should provide more space for user?s profile and medium of communication for its user. In order to present the enhancements, a framework is developed. The framework consists of five components which are academic information system, mobile service/webcast, learning portfolio, knowledge management engine, websites/emails/blogs and knowledge sharing tools. The social network features are embedded into the knowledge sharing tools components. The features are Status Update, Message, Media Sharing, Notes, Share, Like, Quote, Mention, Hashtag and Trends. The improvements on existing features with embed social network features will enhance knowledge sharing e-learning.